2016
DOI: 10.30638/eemj.2016.089
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water Flow Rate on Cooling Effectiveness and Air Temperature Change in Evaporative Cooling Pad Systems

Abstract: In this study, it was aimed to determine the relationship between the temperature decrease of the air passing through the pad and flow rate of pad wetting water for pad evaporative cooling. In the experiments, a commercially available cellulose based evaporative cooling pad (CELdek ® 7060-15 pad) was used. Experiments were conducted at three different water flow rates (2 L min -1 m -2 ; 4 L min -1 m -2 and 6 L min -1 m -2 ) and two different air velocities (1.0 m sec -1 and 1.5 m sec -1 ). The temperature decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The weekly mean values for saturation efficiency during the experimental period were 73.75%, 71.3%, and 70.63% for water flow rates of 4.76, 5.56, and 6.35 L min -1 m -2 , respectively. These findings are similar to those ofKaraca et al (2016). Three multiple regression equations were developed to describe the relationship between SE and outdoor temperature (Tdb,o), outdoor relative humidity (RHo), and temperature of the pad (Tp) for the various water flow rates.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…The weekly mean values for saturation efficiency during the experimental period were 73.75%, 71.3%, and 70.63% for water flow rates of 4.76, 5.56, and 6.35 L min -1 m -2 , respectively. These findings are similar to those ofKaraca et al (2016). Three multiple regression equations were developed to describe the relationship between SE and outdoor temperature (Tdb,o), outdoor relative humidity (RHo), and temperature of the pad (Tp) for the various water flow rates.…”
supporting
confidence: 73%
“…The pad face air velocity should range between 0.5 and 1.5 m s -1 ( Dağtekin et al, 2011). Karaca et al (2016) studied the relationship between the cooling effect and the pad water flow rate (2, 4, and 6 L min -1 m -2 ) and two different pad air velocities (1.0 and 1.5 m s -1 ). The cooling effect and saturation efficiency values were the lowest at a water flow rate of 6 L min -1 m -2 , but they also were relatively similar at water flow rates of 4 and 2 L min -1 m -2 .…”
Section: Introductionmentioning
confidence: 99%
“…Adult chickens body temperature varies between 39 and 40 o C. Poultry house indoor temperature has an immediate impact on poultry, depending on how well it is monitored and controlled. Karaca et al (2016) found that cooling efficiency and the reduction temperature of the air passing through the pad were lower at water flow rate of 6 l/min.m 2 . The most adequate water flow rate for the experimental conditions was considered 4 l/min.m 2 .…”
Section: Introductionmentioning
confidence: 94%
“…The maximum values were 10, 11.5 and 8.8 o C under water flow rates of 2, 4 and 6 l/min.m 2 , respectively at 13.00 pm. The most adequate water flow rate for the experimental conditions was considered 4 l/min.m 2 according to Karaca et al (2016). The decrease in temperature reduction at 6 l/min.m 2 With regard to using indirect evaporative cooling system (IEC), it was seen that increasing water flow rates from 2 to 6 l/min.m 2 gave inverse results of temperature reduction.…”
Section: Temperature Reductionmentioning
confidence: 99%
“…The results clarified that the average daily cooling efficiency values during June, July and August were determined by 77.4%, 75.6% and 79.5%, respectively. Karaca et al (2016) determined the relation between the temperature decrease of the passing air through cellulose based pad and the water flow rate of pad moistening in the evaporative cooling pad systems. Values of cooling efficiency and the temperature decrease of the air passing through the pad were lower at water flow rate of 6 L/min.m 2 , while they were close to each other at (2 and 4 L/min.m 2 ).…”
mentioning
confidence: 99%